The Influence Of Financial Education In Social Organizations (Family) On Personal Financial Management Of Students Of The Faculty Of Economics And Business At University State Of Makassar - Anwar Anwar (International Forum of Researchers and Lecturers, 2024)
These financial problems are the inability of students to manage their own personal money (monthly money from parents), lack of financial planning habits, lack of financial control by parents. So this journal was made to find out whether there is an influence of financial education in social (family) organization on the personal financial management of undergraduate students at the Faculty of Economics and Business, Makassar State University. This type of research is causal associative research, or a causal relationship with a quantitative approach. This can be seen from the probability (sig.) = 0.009 ttable = 2.676 > 1.998 and from the probability (sig.) = 0.000 ttable (4.158 > 1.998). So that it is known that the influence of family finances and financial literacy together has a positive and significant effect on personal financial management and also the influence of family finances has a positive and significant effect on the personal financial management of S1 students of Management, Department of Economics, Makassar State University.